Digitalisasi dan Perubahan Pola Komunikasi Keluarga Komunitas Kajang Luar - Muzakkir, Nurul Annisa; Subhan, Dwiyani; Prayogi, Ivan; Awaru, Andi Octamaya Tenri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explore the impact of digitalization on family communication in the Kajang Luar Community, focusing on adaptation, problems, and its influence on harmony and the preservation of local cultural values. A descriptive qualitative approach was used with four informants from various family members who actively use digital technology. Data were collected through in-depth interviews, participant observation, and documents, analyzed using the Miles and Huberman model, and validated through member checking. The results show that digitalization, particularly the use of smartphones, WhatsApp, and video calls, facilitates long-distance communication but creates challenges such as over-dependence, reduced face-to-face interaction, and conflict. Nevertheless, Kajang Luar families have successfully adapted by maintaining cultural values through Pasang ri Kajang and gadget usage guides, and utilizing technology to introduce traditions. This study reveals social changes due to modernization and the importance of technology management for family harmony and cultural preservation